2006
DOI: 10.1111/j.2006.0030-1299.15200.x
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative reproduction and survival costs in female red deer

Abstract: T. H. 2006. Cumulative reproduction and survival costs in female red deer. Á Oikos 115: 241 Á252.Successful reproduction in a single breeding event has consistently been shown to reduce condition, fecundity and survival to the following breeding season. Few studies have examined the cumulative costs of frequent reproduction on survival. Here we use a dataset of female red deer (Cervus elaphus ) from the Isle of Rum, Scotland, to model survival probability within a mark Árecapture framework. By including both r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
81
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 40 publications
13
81
1
Order By: Relevance
“…Various other measures of quality, for example, longevity or lifetime reproductive success, have been used in previous studies in this and other populations (Espie et al 2004;Blackmer et al 2005;Moyes et al 2006). However, lifetime performance measures are frequently highly correlated (Moyes et al submitted).…”
Section: Methodsmentioning
confidence: 99%
“…Various other measures of quality, for example, longevity or lifetime reproductive success, have been used in previous studies in this and other populations (Espie et al 2004;Blackmer et al 2005;Moyes et al 2006). However, lifetime performance measures are frequently highly correlated (Moyes et al submitted).…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence, reproductive success is expected to decrease future reproduction rather than maternal survival. Survival costs of reproduction are rarely detected in large mammals and then only in juveniles, old females, or in years of very harsh environmental conditions (Clutton-Brock et al 1983, Hamel et al 2010b, Moyes et al 2006, Tavecchia et al 2005. Instead of the expected negative correlation between current and future reproductive success, however, several studies found no or positive correlations (review in Hamel et al 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the covariation between current and future reproductive success depends on the magnitude of both reproductive cost and individual heterogeneity (Wilson and Nussey 2009). Individual heterogeneity may depend on age (Jones et al 2008), early development (Lindström 1999) and environmental condition (Moyes et al 2006), therefore several environmental and individual variables must be accounted for to assess reproductive costs (Hamel et al 2010a). Reproductive costs are often more evident in light (Festa-Bianchet et al 1998, Hamel et al 2010a, primiparous (Green andRothstein 1991, Langvatn et al 2004), and old females (Clutton-Brock et al 1983) at high density or in harsh environments (Bérubé et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Elk that are in poor nutritional condition may be less alert, choose riskier habitats for foraging activity, and be less likely to flee from perceived threats. Similarly, gestation, parturition, and lactation impose high energetic demands on adult females and influence survival rates (Moyes et al 2006). Individual characteristics, including age and body condition, may influence survival of ungulates, with a potentially increased mortality risk for old or young age classes (Solberg et al 2000;DelGiudice et al 2002).…”
Section: Introductionmentioning
confidence: 99%